Risk Relevance of Comprehensive Income in Indonesia: The Role of Corporate Social Responsibility, Good Corporate Governance, Tax Avoidance - Ahmad Surya Widyansyah; Amrie Firmansyah; Dani Kharismawan Prakosa; Much. Rizal Pua Geno (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
This study aims to investigate the effect of comprehensive income volatility on idiosyncratic risk and the moderating role of corporate social responsibility disclosure, good corporate governance disclosure, and tax avoidance on this effect. The analysis includes 99 manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. Through purposive sampling, this study obtained 495 observations. To test each hypothesis, this study employs multiple linear regression. Our findings suggest that comprehensive income volatility positively affects idiosyncratic risk. Furthermore, neither corporate social responsibility, corporate governance, nor tax avoidance can moderate the effect of comprehensive income volatility on idiosyncratic risk. This study provides evidence that investors price comprehensive income volatility as an accounting measure of risk into the stock price. This study also demonstrates that the current practice of corporate social responsibility disclosure and good corporate governance fail to dispel investors' concern over volatile comprehensive income. Meanwhile, tax avoidance does not affect investors' perception of risk arising from volatile comprehensive income.